Optimizing Enhancing Cooperative Governance to Reduce Flood Disasters in Bojonegoro Regency: Qualitative Approach and Cooperation Scheme - Widiyarta, Agus (Universitas Sultan Ageng Tirtayasa, 2024)
This research investigates the role of collaborative governance in mitigating flood disasters in Bojonegoro Regency. Using qualitative methods, we comprehensively examine social processes related to flood mitigation. Our study focuses on how the community, business sector, and government can reduce the impact of flooding. Through a case study approach, we find that collaborative governance implementation has not been fully optimized, with governance components often operating independently. To address this, we propose a collaboration system that includes joined-up government, issue response networks, communities of shared mission, and strategic alliances. By enhancing collaboration, we aim to improve flood disaster mitigation in Bojonegoro Regency, leveraging all available resources and expertise. Community involvement will contribute to building a more resilient ecosystem prepared for future disasters. Implementing these cooperative programs is envisaged to enhance flood catastrophe mitigation in Bojonegoro Regency. Effective collaboration between various elements of governance will ensure that all available resources and expertise can be optimally utilized. This study contributes to the field by emphasizing the importance of collaborative governance in disaster management and resilience.